Chemical Analysis of Firearms, Ammunition, and Gunshot Residue, Second Edition. - Smyth Wallace, James (London : Taylor and Francis, 2017)
"Since publication of the first edition, there have been changes in primer compositions and the particle classification system. Such changes are fully covered in addition to updated information on evidence collection, testing methods, and best practices in techniques. Two new chapters cover interesting/ unusual firearms cases as well as a controversial, landmark Australian case involving inorganic and organic gunshot residue. While the suspect was initially convicted of murder, the ruling was subsequently overturned The case clearly illustrates the dangers of incorrect forensic evidence and the need for careful training of forensic scientists. This new edition will fill that void."--Provided by publisher.
Chapter 1 Definitions / James Smyth Wallace -- section I Introduction -- chapter 2 History of Gunpowder / James Smyth Wallace -- chapter 3 History of Ignition Systems / James Smyth Wallace -- chapter 4 History of Bullets / James Smyth Wallace -- chapter 5 History of Ammunition / James Smyth Wallace -- chapter 6 History of Firearms / James Smyth Wallace -- section II Historical Aspects of Firearms and Ammunition -- chapter 7 Cartridge Cases / James Smyth Wallace -- chapter 8 Primer Cups (Caps) / James Smyth Wallace -- chapter 9 Priming Compositions / James Smyth Wallace -- chapter 10 Propellants / James Smyth Wallace -- chapter 11 Projectiles / James Smyth Wallace -- chapter 12 Complementary Ammunition Components / James Smyth Wallace -- chapter 13 Caseless Ammunition / James Smyth Wallace -- chapter 14 Blank Ammunition / James Smyth Wallace -- chapter 15 Firearm Construction Materials / James Smyth Wallace -- section III Chemical Aspects of Firearms and Ammunition -- chapter 16 Firearm Discharge Residue Detection Techniques / James Smyth Wallace -- chapter 17 Properties of Firearm Discharge Residue / James Smyth Wallace -- section IV Firearm Discharge Residue -- chapter 18 Scenes of Crime Experiences / James Smyth Wallace -- chapter 19 Objectives, Sampling Procedures, Instrumentation, and Conditions / James Smyth Wallace -- chapter 20 Particle Classification Scheme / James Smyth Wallace -- chapter 21 Casework Related Tests / James Smyth Wallace -- chapter 22 Analysis of Ammunition / James Smyth Wallace -- chapter 23 Ammunition Containing Mercury / James Smyth Wallace -- chapter 24 Lead Free Ammunition / James Smyth Wallace -- section V Experimental -- chapter 25 Firearm Discharge Residue Sampling / James Smyth Wallace -- chapter 26 Sampling of Skin and Clothing Surfaces for Firearm Discharge Residue / James Smyth Wallace -- chapter 27 Development of a Method for Organic Firearm Discharge Residue Detection / James Smyth Wallace -- chapter 28 Consequences of Incorrect GSR Evidence / James Smyth Wallace -- section VI Suspect Processing Procedures.
OCLC-licensed vendor bibliographic record.
Keywords: Chemistry, Forensic; Firearms; Ammunition